2022
DOI: 10.1007/978-3-030-98404-5_39
|View full text |Cite
|
Sign up to set email alerts
|

The Value of eCoaching in the COVID-19 Pandemic to Promote Adherence to Self-isolation and Quarantine

Abstract: A Digital electronic Coach (eCoach) app was built and evaluated during the Covid-19 pandemic in The Netherlands. Its aim was to provide support for AQ1 individuals that had to either quarantine or self-isolate after a positive corona test or an indication of a heightened risk of infection. The coach ("IsolationCoach"), AQ2 its value and uses were evaluated in 29 semi-structured interviews with individuals who had quarantined or isolated themselves or were part of the general Dutch public. Three main findings e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Users expected and indicated that they desired more of the app. A study by Blasimme et al [ 16 ] shows that adding new features may “be seen as one way to deliver more personal utility to app users, thus incentivizing participation.” Instead of adding features, the reopening of society was, for example, facilitated by a separate app “CoronaCheck,” and the needs around the psychological aspects of isolation were not met at all [ 17 ]. Thus, the opportunity to enhance the CM app was missed, which the German “CoronaWarn,” for example, used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Users expected and indicated that they desired more of the app. A study by Blasimme et al [ 16 ] shows that adding new features may “be seen as one way to deliver more personal utility to app users, thus incentivizing participation.” Instead of adding features, the reopening of society was, for example, facilitated by a separate app “CoronaCheck,” and the needs around the psychological aspects of isolation were not met at all [ 17 ]. Thus, the opportunity to enhance the CM app was missed, which the German “CoronaWarn,” for example, used.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of leadership and fragmentation in governance (between the Dutch Ministry of Health, Welfare and Sport, MHS, and local government) caused distrust in the COVID-19 measurements. Besides, there was no attention by the Dutch Ministry of Health, Welfare and Sport in press conferences to the added value of the CM app, for example, to use the app as an instrument that facilitates reopening society when people increasingly come into contact with others (van’t Klooster et al [ 17 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Van ‘t Klooster ( 19 ), a digital self-isolation electronic coach (e-Coach) app was built and evaluated during the COVID-19 pandemic. Its aim was to support individuals who had to either quarantine or self-isolate after a positive coronavirus test.…”
Section: Resultsmentioning
confidence: 99%
“…The e-Coach, named IsolationCoach, gradually and conditionally provides relevant information (as opposed to conventional paper pamphlets/emails). Through a holistic patient view ( 19 ) and Socratic method ( 20 ) styled form of self-reflection, it provided emotional support to its users.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation